Student Teachers’ Resilience During The COVID-19 Pandemic: Navigating Remote Teaching Practice - Shange, Florence Mamoroleng; de Jager, Sarina (Research in Social Sciences and Technology- OpenED Network, 2024)
This article explores student teachers’ resilience during the COVID-19 pandemic and their ability to thrive in online teaching practice. Amid the pandemic’s unprecedented challenges, student teachers exhibited remarkable adaptability in navigating the shift to remote teaching. Through qualitative research and thematic analysis, this article delves into student teachers’ experiences, highlighting their positive encounters with online teaching methodologies and tools. The findings underscore the importance of resilience and adaptability in the dynamic field of education, emphasising the valuable skills student teachers attained through their engagement with online teaching. Furthermore, the article explores the advantages of online practical assessments, shedding light on innovative evaluation methods that may shape future educational practices. Overall, the insights gleaned from this research contribute to a deeper understanding of student teachers’ experiences during times of educational transformation. Recommendations are also offered to integrate online teaching methods into teacher training programmes to enhance these students’ resilience and adaptability in the face of adversity.